Paradoxes of female affirmation: curing the mental illness of the modern Indian woman in Dear Zindagi - Suliman, Faatima (My University, 2023)
In examining the Bollywood film Dear Zindagi this study explores the ways in which the progressive narrative of women empowerment is complicated through themes of mental illness and mental health. Furthermore, this study explores modern patriarchy as a concept used to control and manage femininity, further complicating feminist narratives. Theoretically centered within literature on feminism, Bollywood, mental illness, patriarchy, and the bildungsroman, this study examines the influence modern patriarchal narratives have on redefining feminist narratives to fit modern society and how Dear Zindagi is able to progress as a feminist narrative.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Curing the mental illness; Female affirmation; Indian woman